GEOLOGICAL STRUCTURE AND CHARACTERSTICS OF COMPOSITION MATTER OF ОLIVINE MELTEIGITE OF BOLYARSKIY DAYKE (VOLYN MEGABLOC OF THE UKRAINIAN SHIELD) - Baran, A.; Geyko, Yu.; Zagnitko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the Volhynia block of the Ukrainian Shield found out the new body of alkaline ultrabasite – оlivine melteigite. After petrographic, petrochemistric and found out geochemical characteristics breeds similar to before found out the alkaline ultrabasites of blocke. In Bolyarskiy of іntrusive found out mantle xenogenous minerals, thus first in the rocks of similar class of pirope and xenolithes mantle peridotites. It goes to show that initial magma of оlivine melteigites was engendered on depths near to the generation of kimberlite magme and these breeds can be one of sources of dilatation of minerals-indicators of diamond in the sedimentary deposits of the probed territory.